Cultural heritage tourism development strategy in Bogor Regency - Tutut Sunarminto; Joko Mijiarto (Jurnal Pariwisata Pesona, 2022)
Bogor Regency has a variety of cultural heritage, but this potential has not been optimized as a tourist attraction. The purpose of this study is to develop a cultural heritage-based tourism development strategy in Bogor Regency. The research was conducted in December 2020 – January 2021 with literature studies. The study locations focused on the 16 sub-districts that were selected the lowest Human Development Index score and designated as cultural tourism areas. The strategy for developing cultural heritage tourism is carried out by SWOT analysis. Bogor Regency has 29 cultural tourism attractions spread across 13 of the 16 study locations. The cultural heritage has a different story related to the Tarumanegara Kingdom, Prabu Siliwangi, Banten Kingdom, Ir. Soekarno, the Dutch and the Prehistoric Period. Based on the results SWOT analysis, the right strategy to be applied in the development of cultural tourism in Bogor Regency is the S-O strategy.